Impact of ritual pollution on lactation and breastfeeding practices in rural West Bengal, India - Bandyopadhyay Mridula (BMC, 2009)
Abstract Background Breastfeeding in India is universal and prolonged. Several cultural practices are associated with lactation and breastfeeding in India, mainly revolving around the concept of ritual purity and 'hot and cold' foods, food avoidance, restricted diet after childbirth, and remaining in seclusion for a certain time period because of the polluting effects of childbirth. This study on breastfeeding practices explored how the concept of ritual pollution influenced practices after delivery, including during lactation and breastfeeding. Methods The study was conducted in four villages of West Bengal State in India, representing different levels of socioeconomic development, religion, and caste/tribe from September 1993 to April 1994. One hundred households with one woman respondent from each household were selected from each village. Both qualitative and quantitative methods were employed for data collection. A survey questionnaire was administered to 402 respondents and in-depth interviews were conducted with 30 women in the reproductive age group (13-49 years), and 12 case studies were documented with women belonging to different caste, religious, and tribal groups. Results Belief in 'impurity and polluting effects of childbirth' necessitated seclusion and confinement of mothers after childbirth in the study villages. Breastfeeding was universal and prolonged, and food proscriptions were followed by mothers after childbirth to protect the health of their newborn. Initiation of breastfeeding was delayed after birth because of the belief that mother's milk is 'not ready' until two-to-three days postpartum. Generally, colostrum was discarded before putting the infant to the breast in the study villages. Breastfeeding lasted up to five years, and the majority of women in the sample introduced supplementary food before six months. Most infants in the study villages were given a prelacteal feed immediately after birth, only a small number of women (35) exclusively breastfed - after giving a prelacteal feed - until six months in the study villages. Conclusion Cultural and traditional practices have considerable implications on lactation and breastfeeding, and in the overall well-being and health of mothers and infants. Breastfeeding programs should take into account traditional beliefs and concepts when communicating with families about practices such as food restriction and food avoidance.